PENGARUH LONG DEBT EQUITY RATIO DAN CURRENT RATIO TERHADAP RETURN SAHAM DENGAN RISIKO INVESTASI SAHAM SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2020 - Arifah, Khoiratin; Wahyuni, Ika; Pramitasari, Triska Dewi (Fakultas Ekonomi dan Bisnis, 2022)
Pharmaceutical company is a type of company that in its operational activities produces medicinal products for health, unlike trading companies that sell products.This situation will provide an opportunity for investors to invest in the company.The purpose of this study was to determine the effect of Long debt equity ratio and Current ratio on stock returns with stock investment risk as an intervening variable in Pharmaceutical Companies listed on the Indonesia Stock Exchange for the 2017-2020 period.The population in this study were all pharmaceutical companies listed on the Indonesia Stock Exchange for the 2017-2020 period as many as 12 companies.The sampling technique was determined by purposive sampling.Analysis of hypothesis testing data in this study using the Structural Equation-Partial Least Square (PLS-SEM) method. Long Debt Equity Ratio has a significant negative effect on stock investment risk.Current Ratio has a negative but not significant effect on stock investment risk,Long Debt Equity Ratio has a negative but not significant effect on stock returns,Current Ratio has a positive but not significant effect on stock returns,Stock investment risk has a significant positive effect on stock returns,The results of the indirect effect hypothesis test show that the Long Debt Equity Ratio has a significant negative effect on stock returns through stock investment risk,Current Ratio has a negative but not significant effect on stock returns through stock investment risk.